Radon Concentrations in Indoor and Outdoor Environments of Atomic Energy Centre Dhaka, Bangladesh, and Concomitant Health Hazards - Pervin, Shikha; Yeasmin, Selina; Khandaker, Mayeen Uddin; Begum, Afia (Frontiers in Nuclear Engineering, 2022)
Realizing the non-negligible health hazards due to radon exposure, the present study was carried out to measure the radon concentrations in indoor and outdoor environments of Atomic Energy Centre Dhaka (AECD), Bangladesh. A portable electrostatic radon-measuring device (RAD7) was used to determine the indoor radon levels in different laboratories of AECD, and a RAD7 detector with a stainless steel soil probe was employed to measure the soil gas radon in the surrounding areas of the AECD campus. The indoor radon concentration in various laboratories was found to vary from 11 ± 7 Bq/m3 to 360 ± 180 Bq/m3 with an average of 63 ± 33 Bq/m3. Overall, the average indoor radon level shows below the action level (300 Bq/m3) recommended by ICRP publication-126 for homes and workplaces. However, the laboratories having poor ventilation show a relatively higher radon level. The average soil gas radon concentration at different depths of 15 cm, 35 cm, and 55 cm was found to be 0.07 ± 0.01 kBq/m3, 2.31 ± 0.31 kBq/m3, and 22.5 ± 1.4 kBq/m3, respectively. The calculated average annual effective dose due to the inhalation of indoor radon in home and workplaces was found to be below the ICRP recommended value of 10 mSv/y. The present results could serve as a reference radon level in the indoor and outdoor environment in Dhaka city, Bangladesh.